Se@Albumin nanoparticles ameliorate intestinal mucositis caused by cisplatin via gut microbiota-targeted regulation. Issue 25 (21st June 2021) - Deng, Liping; Zeng, Hongliang; Hu, Xueying; Xiao, Mengqing; He, Dong; Zhang, Yao; Jin, Yi; Hu, Yibo; Zhu, Yuxing; Gong, Lian; Wang, Zhanwang; Xiang, Liang; et al.
Abstract : Chemotherapy-associated intestinal mucositis is still one of the major challenges in the first-line clinical cancer treatment. Abstract : Chemotherapy-associated intestinal mucositis is still one of the major challenges in the first-line clinical cancer treatment. Selenium element has shown health benefits on enteritis upon uptake in trace amounts; however, it was limited because of its narrow safety margin. In this work, a new form of Se@Albumin complex nanoparticles (Se@Albumin NPs) was developed by self-assembly of denatured human serum albumin and selenite salts. Se@Albumin NPs significantly improve intestinal mucositis induced with cisplatin (CDDP) in a mouse model via attenuating the level of intestinal oxidative stress, reducing intestinal permeability, and relieving gastric dysmotility. It is very interesting that the restoration of anti-inflammatory bacteria ( Bacteroidetes and Firmicutes ) and reduced abundance of proinflammatory bacteria ( Escherichia ) contributed to the reduction of intestinal mucositis by Se@Albumin NPs in mice. In addition, the fecal microbiota transplantation (FMT) with materials from Se@Albumin NP-treated mice significantly protected pseudo-aseptic mice from CDDP-induced intestinal mucositis. In conclusion, our findings showed that Se@Albumin NPs can significantly improve CDDP-induced intestinal mucositis, and its function may be directly mediated by gut microbiota regulation, which will provide new helpful information for clinical treatment.